2005
DOI: 10.4049/jimmunol.174.7.4090
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of CD45 on Suppressive/Regulatory T Cells Leads to the Abrogation of Their Suppressive Activity In Vitro

Abstract: CD4+CD25+ T cells have immunoregulatory and suppressive functions and are responsible for suppressing self-reactive cells and maintaining self-tolerance. In addition to CD4+CD25+ T cells, there is some evidence that a fraction of CD4+CD25− T cells exhibit suppressive activity in vitro or in vivo. We have shown, using aged mice, that aging not only leads to a decline in the ability to mount CD4+CD25− T cell responses, but, at the same time, renders aged CD4+CD25− T cells suppressive. In this study we report two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Additionally, Zhang et al (41) have shown that raft-excluded CD45 results in sustained ERK activation, enhanced synaptic raft clustering, and increased IL-2 production by T cells following activation. That the positioned exclusion of CD45 or other phosphatases away from the immunological synapse during T cell activation may be altered in Tregs is an intriguing possibility which should be closely examined in light of a recent report demonstrating that the cross-linking of CD45 on Tregs with specific mAbs could abrogate their suppressive action (42).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zhang et al (41) have shown that raft-excluded CD45 results in sustained ERK activation, enhanced synaptic raft clustering, and increased IL-2 production by T cells following activation. That the positioned exclusion of CD45 or other phosphatases away from the immunological synapse during T cell activation may be altered in Tregs is an intriguing possibility which should be closely examined in light of a recent report demonstrating that the cross-linking of CD45 on Tregs with specific mAbs could abrogate their suppressive action (42).…”
Section: Discussionmentioning
confidence: 99%
“…S2). In contrast, the other reagents examined, IL-4 [13], DTA1 [10], 59.32 mAb [11], and conditioned medium from DCs treated with LPS [designated LPS-CM [14]], all of which have the ability to abrogate the suppression by Treg cells, had no co-stimulatory effect on the cell-proliferation. The G3c mAb itself had no effect in the absence of anti-CD3 Ab (less than 500 cpm in all experiments).…”
Section: G3c Can Break the Anergic State Of Treg Cellsmentioning
confidence: 84%
“…Anti-GITR mAb, DTA1 [rat IgG2b [10]], and anti-CD45 mAb, 59.32 [rat IgM [11]], was made from ascites in SCID mice and purified by 50% ammonium sulfate precipitation. The supernatant (SN) from P815 cells transduced with murine IL-4 [12] was used as a source of IL-4.…”
Section: Tumor Cells and Reagentsmentioning
confidence: 99%
“…We have reported that a novel anti-CD45 Ab (59.32) could break the suppressive activity of Treg cells, and, at the same time, act on non-Treg cells as a strong co-stimulatory Ab [8]. The co-stimulatory effect on non-Treg cells was unique (Fig.…”
Section: Persistent Unresponsiveness In the Aged Cd4 T Cell-subsetmentioning
confidence: 97%
“…Mittler. Hybridomas secreting anti-GITR (G3c, rat IgM) or anti-CD45 (59.32, rat IgM) [8] Ab were established in our laboratory. Paraquat dichloride was purchased from Dr. Ehrenstorfbr GmbH (Augsburg, Germany).…”
Section: Abs and Reagentsmentioning
confidence: 99%